Analysis of stone mastic asphalt (SMA) slab dimensions for evaluation of the newly developed roller compactor (Turamesin) - Mohd Jakarni, Fauzan (Universiti Putra Malaysia Press, 2010)
Stone Mastic Asphalt (SMA) is one type of asphalt mixture which is highly dependent on the method of compaction as compared to conventional Hot Mix Asphalt (HMA) mixture. A suitable laboratory compaction method which can closely simulate field compaction is evidently needed as future trend in asphalt pavement industry all over the world is gradually changing over to the SMA due to its excellent performance characteristics. This study was conducted to evaluate the SMA slab mixtures compacted using a newly developed Turamesin roller compactor, designed to cater for laboratory compaction in field simulation conditions. As the newly developed compaction device, there is a need for evaluating the compacted slab dimensions (which include length, width, and thickness), analyzing the consistency of the measured parameters to verify the homogeneity of the compacted slabs and determining the reliability of Turamesin. A total of 15 slabs from three different types of asphalt mixtures were compacted, measured, and analyzed for their consistencies in terms of length, width, and thickness. Based on study the conducted, the compacted slabs were found to have problems in terms of the improperly compacted section of about 30 mm length at both ends of the slabs and the differences in the thickness between left- and right-side of the slab which were due to unequal load distribution from the roller compactor. The results obtained from this study have led to the development of Turamesin as an improved laboratory compaction device.